THE INFLUENCE OF INFRASTRUCTURE INEQUALITY AND CAPITAL ON HUMAN DEVELOPMENT COMPONENTS IN DISTRICS/CITIES OF WEST NUSA TENGGARA PROVINCE 2017-2021 - Puspitasari, Sava Amanda; Deky Aji Suseno (Business and Economic Analysis Journal, 2025)
The inequality in education and health infrastructure has resulted in human development indicators not being achieved optimally. Infrastructure and spending in the education and health sectors have increased but the average length of schooling and life expectancy are low, while GRDP per capita tends to decrease from 2017 to 2021. The purpose of this study is to determine and analyze the effect of infrastructure inequality and government spending on education and health on human development. The results of the analysis show that the panel data regression estimation. In equation I, infrastructure inequality and education spending partially affect the average years of schooling. In equation II, health spending and health infrastructure inequality partially affect life expectancy. In equation III, education infrastructure inequality and life expectancy partially negatively affect GRDP per capita. Education and health expenditure, average years of schooling, and health infrastructure inequality partially have no effect on GRDP per capita. Suggestions that researchers provide based on the results of the study are to build equitable education and health infrastructure according to community needs. Effective and efficient use of education and health expenditure budgets according to community needs.